Motility of single one-headed kinesin molecules along microtubules. - Inoue, Y (2001)
The motility of single one-headed kinesin molecules (K351 and K340), which were truncated fragments of Drosophila two-headed kinesin, has been tested using total internal reflection fluorescence microscopy. One-headed kinesin fragments moved continuously along the microtubules. The maximum distance traveled until the fragments dissociated from the microtubules for both K351 and K340 was approximately 600 nm. This value is considerably larger than the space resolution of the measurement system (SD approximately 30 nm). Although the movements of the fragments fluctuated in forward and backward directions, statistical analysis showed that the average movements for both K340 and K351 were toward the plus end of the microtubules, i.e., forward direction. When BDTC (a 1.3-S subunit of Propionibacterium shermanii transcarboxylase, which binds weakly to a microtubule), was fused to the tail (C-terminus) of K351, its movement was enhanced, smooth, and unidirectional, similar to that of the two-headed kinesin fragment, K411. However, the travel distance and velocity of K351BDTC molecules were approximately 3-fold smaller than that of K411. These observations suggest that a single kinesin head has basal motility, but coordination between the two heads is necessary for stabilizing the basal motility for the normal level of kinesin processivity.